2018
DOI: 10.1093/gbe/evy082
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomics in Two Bivalve Species Offers Different Perspectives on the Evolution of Sex-Biased Genes

Abstract: Comparative genomics has become a central tool for evolutionary biology, and a better knowledge of understudied taxa represents the foundation for future work. In this study, we characterized the transcriptome of male and female mature gonads in the European clam Ruditapes decussatus, compared with that in the Manila clam Ruditapes philippinarum providing, for the first time in bivalves, information about transcription dynamics and sequence evolution of sex-biased genes. In both the species, we found a relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 97 publications
(123 reference statements)
4
17
0
Order By: Relevance
“…Similar results were obtained by Havird and Sloan (2016) who analyzed 84 eukaryotic taxa and concluded that transcript abundance cannot be responsible for dN/dS. Moreover, Ghiselli et al (2018)-who analyzed sequence evolution and transcription level in sex-biased nuclear genes-already discussed the need to be careful in searching for a causal correlation between these two variables, and here, we confirm no evidence for E-R correlation. Also, our results show that transcription level of both nuclear and mitochondrial subunits is highly variable, and it is not uniform even across samples within species-despite using the same tissue at the same stage of life cycle.…”
Section: The Relationship Between Transcription Level and Rate Of Psupporting
confidence: 90%
See 4 more Smart Citations
“…Similar results were obtained by Havird and Sloan (2016) who analyzed 84 eukaryotic taxa and concluded that transcript abundance cannot be responsible for dN/dS. Moreover, Ghiselli et al (2018)-who analyzed sequence evolution and transcription level in sex-biased nuclear genes-already discussed the need to be careful in searching for a causal correlation between these two variables, and here, we confirm no evidence for E-R correlation. Also, our results show that transcription level of both nuclear and mitochondrial subunits is highly variable, and it is not uniform even across samples within species-despite using the same tissue at the same stage of life cycle.…”
Section: The Relationship Between Transcription Level and Rate Of Psupporting
confidence: 90%
“…Transcriptome data of mature gonads from 12 individuals (six females and six males) of R. decussatus and 12 individuals (six females and six males) of R. philippinarum were retrieved from Ghiselli et al. (). Raw reads and transcriptome assembly from both experiments are available on NCBI, under BioProjects PRJNA68513 ( R. philippinarum ) and PRJNA170478 ( R. decussatus ); further data are available on figshare: https://doi.org/10.6084/m9.figshare.5398618.v1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations